Managing high reliability organizations (HROs): insights from HRO operations - Schulman, Paul (Henry Stewart Talks, 2012)
HRO research beginnings, High reliability challenges, Special features of HROs, HRO contrasts with conventional organizations, HROs and precursor zone protection, Managing and bounding organizational fluctuations, High reliability strategy in stable and unstable environments, Reliability in networked infrastructures, High reliability and cognitive skills, Organizational requirements for high reliability, HRO features to consider, High reliability in organizations of the future